Nonlinear fiber optics - Agrawal, G. P. (Govind P.), 1951- (Oxford : Academic, 2013)
Since the 4th edition appeared, a fast evolution of the field has occurred. The fifth edition of this classic work provides an up-to-date account of the nonlinear phenomena occurring inside optical fibers, the basis of all our telecommunications infastructure, as well as being used in the medical field. Reflecting the big developments in research, this new edition includes major new content: slow light effects- Which offers a reduction in noise and power consumption, and more ordered network traffic- stimulated Brillouin scattering, vectorial treatment of highly nonlinear fibers, and a brand new chapter on supercontinuum generation in optical fibers. Continues to be industry bestseller providing unique source of comprehensive coverage on the subject of nonlinear fiber optics Updated coverage of intrapulse Raman scattering, four-wave mixing, and Harmonic GenerationIncludes a new chapter excusively devoted to supercontinuum generation in optical fibers.
Note continued: 13.6.1. Spectral-Domain Degree of Coherence -- 13.6.2. Techniques for Improving Coherence -- 13.6.3. Spectral Incoherent Solitons -- 13.7. Optical Rogue Waves -- 13.7.1.L-Shaped Statistics of Pulse-to-Pulse Fluctuations -- 13.7.2. Techniques for Controlling Rogue-Wave Statistics -- 13.7.3. Modulation Instability Revisited -- Problems -- References.
Includes bibliographical references and index.
Keywords: Fiber Optics; Nonlinear optics; Fiber optics; Nonlinear optics